Optimization of Physical Parameters and Analysis of Rock Movement and Deformation Patterns in Deep Strip Mining - Yue Dong; Yuanzhong Luan; Zhaolei Ji; Hengxuan Luan (Applied Sciences, 2022)
China’s shallow coal resources are gradually diminishing, and deep coal resources have slowly become the main energy source. However, the destruction mechanism and evolution of deep rock formation structure are not clear, which seriously restricts the exploitation and utilization of deep energy. Here, the optimization of the physical parameters and the deformation law of the overlying rock in a deep mine in Shandong Province were studied with an integrated approach including similar simulation, mechanical analysis, numerical simulation, and measurement verification, etc. First, the paper simplified the rock formation and developed a numerical model using the field exploration data; second, we analyzed the mechanical properties of each rock formation, obtaining the key rock formation that affects the surface deformation of the mining area. Furthermore, we tested the physical parameters of rock formation by using the orthogonal test, optimizing the physical parameters of rock formation with the extreme difference, and variance analysis of the orthogonal test results. Then, using FLAC3D, we conducted numerical calculations for strip mining of deep wells with numerous working faces, analyzing the maximum surface subsidence value, the maximum horizontal movement value of ground surface at different mining depths, and the change in the subsidence coefficient. By analyzing the linkage relationship between the surface phenomenon and deep mining, we obtained the optimal mathematical model of the three and the coal seam mining depth, which revealed the linkage law of “deep formation–earth surface”. Finally, the model relationships of the influence boundary value, maximum subsidence value, maximum horizontal movement value, and mining depth for each rock layer were separately established.